Antecedents of brand tribalism and its influence on purchase intention in the luxury housing market - Tsiu, Nthabiseng (My University, 2018)
The purpose of the study was to determine the antecedents of brand tribalism and its influence on purchase intention in the luxury housing market. A research conceptual model was developed to assess the potential relations between luxury brand preference, corporate philanthropy, social identity, brand fetish, brand tribalism and luxury brand purchase intention. The research objectives and proposed hypothesis were also based on the above-mentioned variables. The study adopted the positivist approach whereby it was quantitative in nature. Research data was collected from 267 willing participants from the Gauteng province in various industries. Their selection for the study was based on convenience sampling. In order to analyse the data the structural equation modelling approach was utilised in which SPSS 24 and AMOS 24 were used. Numerous findings were observed from five hypotheses that were developed for the purposes of the study. The proposed hypotheses were found to be supported and significant except for one. The relationships not significant were those of social identity and brand tribalism. This was also the weakest relationship and suggested that to identify socially; one did not need to be part of a brand tribe. Lastly, recommendations for marketing practitioners, housing market government officials and academicians were provided in the study.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing 19 June 2017
Keywords: Branding (Marketing); Marketing; Group identity